System Biology: A text Book by Klipp - Edda Klipp [et.al...] (Wiley-VCH, 2009)
This advanced textbook is related to the successful previous title by the same authors and has incorporated the suggestions from many lecturers. It is tailored to the needs of an introductory course in Systems Biology and has a companion web site featuring additional material.